Cultivation of fiber nettle (Urtica dioica L.) in an agroforestry system for peat substitution in horticulture - Lewerenz, Laura; Koltermann, Doreen; Langhof, Maren (Frontiers in Agronomy, 2025)
The German Federal Government aims to drastically reduce or even ban the use of peat in growing media in commercial horticulture by 2030. The joined project “Development and evaluation of peat-reduced production systems in horticulture” (ToPGa) explores and evaluates the challenges and effects of the employment of peat substitutes for practical application. For this, a special focus is set on the evaluation of the renewable, locally grown resource fiber nettle (Urtica dioica L.) as a potential peat substituent. In this approach, three fiber nettle genotypes were established in an alley cropping agroforestry system. To evaluate the dependency of the nettle growth on genotype and distance to the tree line, nettle yield was determined over four consecutive years. The differences in yield between different genotypes were not significant in first three years of harvest. In general, genotype L18 showed a higher biomass yield as B13 and Z10. The yield of nettles growing 6 to 12 m from the tree line was significantly higher. We conclude that while all genotypes can tolerate the growing conditions close to the trees, nettle plants gain higher yields when grown further from the tree line with a maximum yield of 11.4 t ha-1 in the fifth year of cultivation. Retted nettle exhibits a low pH and minimal salinity. Nettles accumulate only low amounts of trace elements. Overall, chemical properties vary according to the season of harvest. Annual variations in retted material are not significant.